Penerapan Analytical Network Process Dalam Menentukan Ras Ayam Serama Simple Additive Weighting (SAW) - Wirhan Fahrozi; Samsir Samsir (U-NET Jurnal Teknik Informatika, 2019)
Serama chicken is the result of dwarf chicken crossing and is a new type of ornamental poultry currently popular in Indonesia. So it becomes a consideration for lovers of serama to get information about quality of serama chickens that need to get accurate information about quality of serama chickens that still needs to be discussed for the assessment of serama chickens, therefore the author tries to implement it in the form of a Decision Support System in determining chicken breeds as well as by applying the Simple Additive Weighting method to assist in optimal decision making. So that the expected results of the quality of the serama chicken can help in determining the standard of serama chicken assessment.